O ensino de Filosofia por meio da aprendizagem cooperativa: uma experiência no ensino médio do IFCE Campus Caucaia - Ceará - Custódio, Robson Pontes (2021)
The research entitled “Teachi ng philosophy through cooperative learning: an experience in high school at IFCE Caucaia CE Campus” aims to elect and present the cooperative learning methodology and its applicability on teaching philosophy as a methodology that enables and potentializes the learning of philosophy in a philosophical way. Learning philosophy from philosophizing is a current challenge for those who teach this subject in high schools, and this is the main relevance brought by this research to the whole society, mainly to all of the teachers and/or researchers who take interest in studying the teaching of philosophy and/ or in studying the cooperative learning methodology. Socrates is the thinker that makes the connection, bringing characteristics in common between philosophy, its teaching and the cooperative learning, being, therefore, the master from Athens used to base this research theoretically and philosophically. Besides, a bibliographical research was done on authors who think about the teaching of philosophy and on authors who think about the cooperative learning methodology itself. The method used for conducting this research was, besides the bibliographical one, a field research applied in a class at IFCE Caucaia/ CE Campus, in which the cooperative learning was applied during one semester according to owned instructions and rules suggested after readings and visitations to places where this methodology has already been applied. After this period a questionnaire was given to students with the intention of gathering and analyzing the data. The achieved results bring contributions to the cognitive aspect of the students regarding the learning of philosophy as well as to the development of group and social skills , pointing out to making students who will develop autonomy when they reach the adult age. All of this confirms the demonstration that with the application of the cooperative learning methodology on teaching philosophy, comes to light away of making the learning of philosophy in a philosophical way real inside the classroom, leaving the possibilities so the study of this matter may be deeper bringing contributions of even more reach to the society.